Recovery of Tree Stand After Clear-cutting in the Ural Mountains - Ivanova, N. S. (International Journal of Bio-resource and Stress Management, 2014)
For the mountain forests of the Middle Urals (Russia) recovery of tree stand after clear-cuttings was studied. Two options of the drained habitats have been studied: steep slopes of the southern exposition with small stony soils and the lower parts of gentle slopes with thick soils. For the description of biomass dynamics of pine (Pinus sylvestris L.) and birch (Betula pendula Roth, B. pubescens Ehrh.), their interference in the course of forest stand formation were constructed on the basis of systems that connected logistic equations of the model of their coexistence. We have developed mathematical descriptions of two alternative ecodynamic series of forest vegetation formation in clear-cutting: regeneration of initial forests (after cuttings in cowberry shrub pine forests) and the formation of long-derivative grass-reed grass birch forests (after cuttings in grass pine forests).